Cloning and sequence analysis of a novel hemolysin gene (vllY) from Vibrio vulnificus. - Chang, T M (1997)
A gene (vllY) encoding a novel hemolysin of Vibrio vulnificus CKM-1 has been cloned and sequenced. When the vllY gene was expressed in minicells, a unique peptide of approximately 40 kDa was identified. Subcellular fractionation of Escherichia coli cells carrying the vllY gene indicated that the VllY protein was distributed in both the cytoplasmic and the periplasmic fractions, with the notable ability to appear in the latter compartment. Nucleotide sequence analysis predicted a single open reading frame of 1,071 bp encoding a 357-amino acid polypeptide with an estimated pI of 5.02. The deduced amino acid sequence of VllY showed high similarity to the sequence of legiolysin, responsible for hemolysis, pigment production, and fluorescence in Legionella pneumophila. The enzyme also exhibited sequence homology to the MelA protein sequence of Shewanella colwelliana and the sequences of 4-hydroxyphenylpyruvate dioxygenase family proteins from various organisms. PCR screening and Southern blotting of V. vulnificus strains revealed that all of the 41 V. vulnificus clinical isolates contained vllY-like genes.